Mortality and revision risk after femoral neck fracture: comparison of internal fixation for undisplaced fracture with arthroplasty for displaced fracture: a population-based study from Danish National Registries - Viberg, Bjarke; Frøslev, Trine; Overgaard, Søren; Pedersen, Alma Becic (Acta Orthopaedica, 2020)
Background and purpose — Hemiarthroplasty has lower reoperation frequency and better mobilization compared with internal fixation (IF) in patients with undisplaced femoral neck fractures (FNF), which might translate into lower mortality. In this population-based cohort study we compare the risk of mortality and reoperation in undisplaced FNF treated with IF and displaced FNF treated with arthroplasty in patients older than 70 years old. We assume that, per se, there is no difference in mortality risk between patients with a displaced and an undisplaced FNF. Patients and methods — Hip fracture patients were identified in the Danish Multidisciplinary Hip Fracture Registry during 2005–2015. Data on medication, comorbidities, reoperation, and mortality were retrieved from other Danish medical databases. IF and arthroplasty patients were compared with regards to mortality and reoperation up to 5 years postoperatively. We calculated hazard ratios (HR) with 95 % confidence intervals (CI) adjusting for relevant confounders. Results — We included 19,260 FNF treated with arthroplasty and 10,337 FNF with IF. There was an increased risk of mortality for arthroplasty within 30 days, HR 1.3 (95% CI 1.3–1.4), compared with IF but not after 1 and 5 years. Arthroplasty patients had adjusted HRs for reoperation of 0.8 (0.8–0.9) within 1 year, 0.8 (0.7–0.9) within 2 years, and 0.8 (0.8–0.9) within 5 years postoperatively compared with IF. Interpretation — Patients treated for a displaced FNF with arthroplasty had a higher risk of 30-day mortality compared with patients who had an undisplaced FNF treated with IF. It has to be considered that there were baseline differences in the groups but there was no difference in mortality risk up to 5 years post-surgery. Concerning reoperation, patients with a displaced FNF treated with arthroplasty had a lower risk of reoperation compared with IF for undisplaced FNF.